Fifty years of the European medicines regulatory network: reflections for strengthening intra-regional cooperation in the Region of the Americas - Martin Harvey Allchurch; Dirceu Brás Aparecido Barbano; Marie-Hélène Pinheiro; Janis Lazdin-Helds
ABSTRACT This report considers how the experience of the European regulatory system might be applied to help strengthen the regulatory systems for medicines in the Region of the Americas. The work of the European Medicines Agencies (EMA) is carried out through its scientific committees, composed of members from European Economic Area countries. A robust legal framework allows EMA to coordinate resources from Member States' competent authorities, including, for example, assisting candidate countries as they prepare to join the European Union (EU). Capacity-building programs help countries adjust their regulatory systems ahead of full participation in the European medicines regulatory network. These programs facilitate adoption of common technical requirements, identify areas where action might be needed to ensure the smooth transposition of EU pharmaceutical law into national legislation, and prepare candidate countries for participation in EMA committees and the European regulatory network. The methodology of these programs could be of potential interest to the Pan American Health Organization (PAHO), the Regional Office of the World Health Organization for the Americas. Given resolutions adopted by the World Health Assembly and the PAHO Directing Council, there is a strong indication that the countries of the Region of the Americas wish to assemble a system that uses the existing regulatory capacity of some countries to strengthen local regulatory capacities in others.